Independence day [videorecording (DVD)] - Emmerich, Roland; Smith, Will, 1968-; Pullman, Bill; Goldblum, Jeff, 1952- (Twentieth Century Fox Home Entertainment, 2002)
Spaceships appear and wonder turns to terror as they attack cities all over the earth.